2018
DOI: 10.1155/2018/4351674
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-QTOF MS-Based Serum Metabolomic Profiling Analysis Reveals the Molecular Perturbations Underlying Uremic Pruritus

Abstract: As one of the most troublesome complications in patients with chronic renal disease, the etiology of uremic pruritus remains unknown, and the current therapeutic approaches are limited and unsatisfactory. To identify potential biomarkers for improving diagnosis and treatment and obtain a better understanding of the pathogenesis of uremic pruritus, we compared serum metabolome profiles of severe uremic pruritus (HUP) patients with mild uremic pruritus (LUP) patients using ultraperformance liquid chromatography-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A more sophisticated analysis of plasma from a larger number of patients might however identify related chemical structures which can trigger pruritus. In this regard, a previous metabolomic analysis did show separation in the solute profiles of patients with more and less pruritus but did not identify individual solutes or common chemical structures with which pruritus was associated [17]. Finally, the measurement of pruritus is subjective.…”
Section: Plos Onementioning
confidence: 91%
“…A more sophisticated analysis of plasma from a larger number of patients might however identify related chemical structures which can trigger pruritus. In this regard, a previous metabolomic analysis did show separation in the solute profiles of patients with more and less pruritus but did not identify individual solutes or common chemical structures with which pruritus was associated [17]. Finally, the measurement of pruritus is subjective.…”
Section: Plos Onementioning
confidence: 91%
“…Another study used ultraperformance liquid chromatography coupled with time-of-flight mass spectrometry (UPLCMS) for metabolic profiling of serum from CKD-aP patients to find diagnostic biomarkers for uremic pruritus, if any. They divided the patients into two groups according to the severity of pruritus and found nine metabolites (LysoPE (20:3(5Z,8Z,11Z)/0:0), p-cresol glucuronide, LysoPC(20:2(11Z,14Z)), hypotaurine, 4-aminohippuric acid, LysoPC(16:0), phenylacetic acid, kynurenic acid, and androstenedione) to be responsible for severe CKD-aP [ 28 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Mass spectrometry of lesional skin from atopic dermatitis patients revealed an increase in short-chain LPC species [ 43 ]. Moreover, a recent study found that LPC concentrations are significantly elevated systemically in uremic patients with pruritus [ 44 ]. In our recent study [ 16 ], we demonstrated that LPC, as a novel pruritogen, is robustly pruritic in mice, and that TRPV4 in skin keratinocytes is essential for LPC-induced itch and itch in mice with cholestasis in a model of α-naphthyl-isothiocyanate (ANIT).…”
Section: Trpv4 In Experimental Chronic Itchmentioning
confidence: 99%